A Hidden Treasure in Sakarya from the Westernisation Period: Hand-Drawn Decorations in Taraklı Yunus Pasha Mosque - Gülsen Tezcan Kaya; Esra Durmuş (Sanat Tarihi Yıllığı)
The Yunus Pasha Mosque, located in the Taraklı district of Sakarya province and dating back to the 16th century, was built in the style of Ottoman mosques, consisting of a dome-covered square-planned harbour, and a three-section narthex in front of the northern wall of this harim. The building is important in terms of the decoration program in the Ottoman art of the Westernization Period, with its original hand-drawn works that have survived to the present day. In this research, the old and new versions of the hand-drawn decorations were studied comparatively, as a result of revealing the original patterns before the restoration of 1993 with the mechanical scraping made in the harim during the restoration that was launched by the General Directorate of Foundations in 2023. These decorations were analysed in regard to their style and compositional features, and where they stood in the decorative programme of the Ottoman Westernisation Period was discussed. Flower bouquets, curtain and oil lamp motifs, chain patterns, writing, geometric motifs, and inscribed medallions were hand-drawn on the plaster in the harim of the building, concordant with the decorative programme that started to become fashionable in Ottoman architecture in the 18th century. In addition, the depiction of medallions with their nails as a painting on the wall, which is not encountered in other examples of religious architecture, is an indication of the rich imagination of the artists Black, yellow, brick colour, blue and red constitute the colour scheme of these decorations. When the decorations, which are believed to be the work of local artists, are examined on the basis of their style and composition, two different periods stand out. These periods, dated to the latter half of the 19th century and the early 20th century, are also significant in terms of revealing diverse elements in the decorative programme.